Isolasi Senyawa Metabolit Sekunder Dari Fraksi Aktif Antibakteri Pada Tumbuhan Sirih Merah (Piper porphyrophyllum) - Efdi, Mai; M. Iqbal Alfarisyi; Arifin, Bustanul (Departemen Kimia Universitas Andalas, 2023)
The red betel plant (Piper porphyrophyllum) belongs to the Piperaceae family which is traditionally used to treat various diseases, including headaches, bone pain, chest tightness, leprosy, stomach ache, as well as for various other diseases such as skin diseases and diabetes. In this study, the antibacterial activity was tested for the hexane, ethyl acetate and methanol extracts of red betel nut using the disc diffusion method and the isolation of secondary metabolites from the hexane fraction of red betel nut using column chromatography technique. Determination of the antibacterial activity of the three fractions showed that the methanol extract had better antibacterial activity compared to the hexane extract and ethyl acetate extract. UV spectrum analysis showed 3 bands with absorption of 282 nm in band I, 274.80 nm in band II and 224.80 nm in band III which means that they show characteristics for triterpenoid group compounds. FTIR analysis showed the presence of C-H, CH2, C=O, C-O alcohol and geminal dimethyl functional groups in the isolated compounds.